Armenia fostering the long-term financial viability and sustainability of the Armenian water and sewerage company - Torres, Adrian; Asian Development Bank.; Armenian Water Sewerage Company (Manila Asian Development Bank, 2013)
In 2007, ADB approved a loan of
This paper outlines ADB?s interventions to improve water supply and sanitation services in Armenia through the initial project and the additional financing. It also highlights the rationale behind the structure of a new tariff regime, which is aimed at fostering the long-term financial sustainability of AWSC.
"March 2013."
Publication Stock No. WPS135546
Key sector challenges -- Policy, institutional, and legal reforms -- ADB support to Armenia's Water Sector -- Lesson's learned -- The next chapter for the Armenian Water Sewerage Company.
Keywords: Water resources development -- Armenia; Water-supply management; Sustainable development -- Armenia